HUBUNGAN POWER OTOT TUNGKAI DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP ACCURACY SMASH PADA ATLIT CLUB VOLI PUTERA BMK VC KECAMATAN KANDIS - Sumario, Yunus; Zainur, Zainur; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aims to determine whether there is a relationship between leg muscle power and wrist flexibility on accuracy smash in volleyball club athletes. The sample of this study was male volleyball athletes from Bmk VC, Kandis sub-district, a sample of 18 people. The sampling technique was taken by (total sampling) or the full sampling technique of the male volleyball athletes of BMK VC, Kandis sub-district, totaling 18 people. The results of the correlation of male volleyball athletes bmk vc Kandis sub-district where the first analysis is between X1 and Y where rtab is at a significant level (0.05) = rcount 0.601> rtable 0.482, meaning that the hypothesis is accepted and there is a strong relationship between X1 and Y. X2 and Y, where r_tab is at a significant level (0.05) = rcount 0.929> rtable 0.482 , meaning that the hypothesis is accepted and there is a strong relationship between X2 and Y. The third analysis of X1 and X2 with Y, where rtab is at a significant level É‘ (0.05 ) = rcount 0,600> rtable 0.482, it can be concluded that the relationship between X1 and X2 with Y is very strong.Key Words: Muscle Power and Wrist Flexibility, Accuracy Smash.